حدود وإمكانيات العلاج الجراحي في السرطانة الرئوية البدئية - رومية, دمر (Latakia University Journal -Medical Sciences Series, 2019)
تمت دراسة /135/ مريضاً مصابا ًبالسرطانة الرئوية عولجوا جراحياً في مشفى الأسد الجامعي باللاذقية بين عامي 1991-1998 وتم التركيز في هذه الدراسة على نقطتين : الأولى : وجود نقائل ورمية إلى العقد اللمفية N2 وتأثير ذلك على معدل البقيا لمدة ثلاث سنوات بعد الإستئصال الجراحي للسرطانة الرئوية وتجريف العقد اللمفية . الثانية :ارتشاح الورم وامتداده إلى بعض البنى التشريحية خارج الرئوية سواء كان بالنسبة للورم T3 أو T4 وتأثير ذلك على معدل البقيا بعد الإستئصال الجراحي . درست هاتان النقطتان من عدة زوايا بهدف الإجابة على كون وجود نقائل ورمية إلى العقد اللمفية N2 أو ارتشاح الورم البدئي إلى بعض البنى التشريحية خارج الرئوية تشكلان مضاد استطباب للعمل الجراحي أم لا . النتائج : إن وجود نقائل ورمية إلى العقد اللمفية N2 يسيء إلى الإنذار ومعدل البقيا بعد الاستئصال الجراحي للسرطانة الرئوية . إن امتداد السرطانة الرئوية إلى بعض البنى التشريحية خارج الرئوية للورمين) T3 , (T4 لا يؤثر على معدل البقيا لمدة ثلاث سنوات . في حال إجراء العلاج الجراحي الجذري لهؤلاء المرضى . إن وجود نقائل ورمية إلى العقد اللمفية N2 وكذلك امتداد الورم البدئي إلى بعض البنى التشريحية خارج الرئوية للورمين T3 , T4 لا يشكلان مضاد استطباب للعمل الجراحي حيث ينصح في مثل هذه الحالات بإجراء الإستئصال الجذري مع تجريف العقد اللمفية وإجراء العلاج الشعاعي والكيميائي قبل أو بعد العلاج الجراحي حسب كل حالة . Our study included /135/ patients suffering from primary bronchical Cancer , treated surgically at AL-ASSAD University Hospital in Lattakia during the period 1991-1998 . Two important Issues were discussed in details : The 1 st one :the presence of lymph nodes metastasis N2 and its influence on the prognosis & 3 years survival rate after surgical treatment of the primary bronchial Cancer and performing lymphadenectomy . The 2 nd issue: Tumor invasion and expansion to some extrapulmonary structures either for T3 or T4 and its effect on the prognosis and 3 years survival rate after surgical management . These two issues were discussed from several points of view in order to answer the main question : whether the presence of N2 Metastasis or the invasion of the Tumor T3,T4 to some extrapulmonary structures are contraindication for surgical treatment or not . Results: 1-the presense of lymph node metastasis N2 will worsen the prognosis and the 3 years survival rate after surgical treatment of bronchial cancer . 2- the invasion of primary bronchial cancer T3,T4 to some extrapulmonary structures will not affect the prognosis and the ( 3) years survival rate after radical surgery . . 3- the presence of LN metastasis N2 and T3,T4 invasion to some extrapulmonary structures are not considered as contraindication for surgical treatment . We advice in such cases to perform radical surgical procedures and lymphadenectomy with pre- or postoperative chemo-radiotherapy.